Millennial Perceptions of Fast Fashion and Second-Hand Clothing: An Exploration of Clothing Preferences Using Q Methodology - Katelyn Sorensen; Jennifer Johnson Jorgensen (Social Sciences, 2019)
Millennials are becoming more conscientious of the products they buy, as well as the social and environmental implications behind them. However, Millennials with low discretionary incomes have limited choices in today’s marketplace, and it is unclear as to how these consumers perceive low-cost apparel options, including fast fashion apparel and second-hand apparel. The purpose of this study is to explore and compare Millennials’ perceptions of inexpensive fast fashion and second-hand apparel. The Q methodology was employed to determine patterns among perceptions. Participants sorted 14 statements describing ideal clothing items into a Q sort grid. The Q sort grid forced participants to rank statements by the degree to which they agree (or disagree). Once the Q sort grid was completed, participants shared their thoughts (qualitatively) as to why they ranked each statement the way that they did. The findings indicate that there are varied perceptions across the Millennial generation, which resulted in the emergence of four distinct factors for both fast fashion and second-hand apparel. The findings of this study are extensive. Fast fashion retailers and consignment shops will need to update their future strategies in order to target the Millennial generation.